2011
DOI: 10.1111/j.1540-8159.2011.03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic Incompetence and Abnormal Heart Rate Recovery Early after Left Ventricular Assist Device Implantation

Abstract: LVAD patients present an impaired CR and an abnormal HRR(1) after implantation, indicating significant cardiac autonomic abnormalities. These alterations seem to remain unaltered 3 months after LVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
(57 reference statements)
4
23
1
Order By: Relevance
“…At maximum load, a mean RER of 1.11 (60.07) and a mean lactate concentration of 3.82 (61.0) mmol/L could be measured. Similarly high levels were attained in comparable studies (RER between 1.07 and 1.26 [10,13,[38][39][40]). As the peak exertion level criterion for CPET in healthy subjects, Kroidl et al (16) recommend an RER of >1.11 and an RER of >1.05 in cardiac patients.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…At maximum load, a mean RER of 1.11 (60.07) and a mean lactate concentration of 3.82 (61.0) mmol/L could be measured. Similarly high levels were attained in comparable studies (RER between 1.07 and 1.26 [10,13,[38][39][40]). As the peak exertion level criterion for CPET in healthy subjects, Kroidl et al (16) recommend an RER of >1.11 and an RER of >1.05 in cardiac patients.…”
supporting
confidence: 61%
“…Table 4 summarizes the results of comparable studies which conducted a CPET shortly after LVAD implantation (90 days). In most investigations, comparably low values were recorded (10,13,25,38,39,41 remained unchanged over time at the same (low) levels (12.66 mL/kg/min after 3-6 months, 10.74 mL/kg/min after 1 year, and 11.18 mL/kg/min after more than 1 year). For comparison, patients after heart transplantation usually reach average values of 17-20 mL/kg/min (60-70% of predicted values) in the long term (45).…”
Section: Cardiopulmonary Exercise Capacitymentioning
confidence: 88%
See 1 more Smart Citation
“…Patients are also seen to have impaired chronotropic reserve and an abnormal heart rate recovery early after continuous-flow LVAD placement, indicating significant cardiac autonomic abnormalities. 11 However, improvement in cardiac sympathetic innervation is noted after LVAD placement in long-term follow-up, suggesting recovery of autonomic function. 12 Under ideal conditions, unloading the LV usually improves systemic hemodynamics but in doing so may have detrimental effects on the RV.…”
Section: Discussionmentioning
confidence: 97%
“…[16][17][18] Two small studies with paired pre-and postimplant VO 2 showed similarly small increases in VO 2 max after 3-6 months of support. 19,20 Recently, Nahumi et al 21 2.0 ± 0.7 Mixed venous oxygen saturation (%) 50.8 ± 12.8 Right ventricular stroke-work index (g/m 2 /beat) 6.9 ± 3.3 Right ventricular failure risk score, n (%) ‡ ≤3 31 (89) 4-5 2 (6) ≥5. 5 2 (6) Plus-minus values are mean ± SD.…”
Section: Discussionmentioning
confidence: 99%